- Analisis Itsbat Nikah Terhadap Perkawinan Kedua Yang Masih Dalam Masa Iddah Berdasarkan Hukum Keluarga Islam Indonesia : - - Dewi Maharani; Bakri, Khairani (Faculty of Law, Universitas Trisakti, 2023)
Itsbat marriage is the legalization of marriage which is carried out in series and submitted to the local religious court. Marriage which was originally only legal before religion became legal before the law by filing itsbat marriage. Formulation of the problem 1. Can itsbat marriage be filed for a second marriage that is still in its infancy Iddah based on Indonesian Islamic Family Law? 2. Is the decision of the Religious Court Number 176/Pdt.P/2022/PA.TNG in accordance with Indonesian Islamic Family Law? This writing was done using normative methods and the nature of descriptive research. The type of data used is secondary data through library research. Data management is carried out in a qualitative way. Drawing conclusions is done in a deductive way. Conclusion that itsbat marriage cannot be filed for a second marriage that is still in its term Iddah because he violated the provisions of Indonesian Islamic Family Law, especially Article 11 of Law Number 1 of 1974 concerning Marriage in conjunction with Article 39 paragraph (1) letter (b) of Government Regulation Number 9 of 1975 concerning Implementation of Law Number 1 of 1974 Jo 153 paragraph (2) letter (b) Compilation of Islamic Law. The decision of the Tangerang Religious Court Number 176/Pdt.P/2022/PA.TNG is not in accordance with Indonesian Islamic Family Law.